Zanzibar Uhuru revolution, two women and the challenge of survival - Chappel, Anne. (CreateSpace Independent Publishing Platform, 2015)
It is 1964, a month after independence celebrations in the spice islands of Zanzibar, off the east coast of Africa. A brutal uprising takes place apparently led by a shadowy figure, John Okello. In the capital, Stone Town, a British official, Mark Hamilton, struggles to help the Sultan?s government survive while protecting his young family. In the countryside, Ahmed al-Ibrahim, a Zanzibari Arab father, faces annihilation and a terrible decision. Fatima is his twelve-year-old daughter, and her life is changed forever by the violence that now sweeps across the islands. Fatima?s survival through this chaos and the thirty years of rule by despotic Presidents takes all her courage and the kindness of other families. Elizabeth, Mark Hamilton?s young daughter, also remembers the day of the Revolution and their escape across the seas. Her story too is touched by tragedy. Fatima and Elizabeth are connected in a way that takes almost fifty years to be revealed. Elizabeth will return to Zanzibar to fulfil her father?s final request. The life journeys of the two women are different. The common link is the day of the Revolution and the act of a desperate man.
Includes index
Keywords: Zanzibar Revolution